Mechanical, thermal and water absorption properties of epoxy/acrylated epoxidized palm oil/montmorillonite nanocomposite - Rohani, Mustapha; Abdul Razak, Rahmat; Rohah, Abdul Majid; Siti Noor Hidayah, Mustapha (AIP Publishing, 2018)
New bio-based epoxy resin were prepared by blending epoxy resin with acrylated epoxidized (AEPO) palm and cured with a Phenalkamines Cardolite NX-2003D bio-based hardener. The various amounts of montmorillonite nanoclay (MMT) at 0.5, 1.0, 1.5 and 2 phr were incorporated in the epoxy - AEPO blend to improve the mechanical and thermal properties of the epoxy/AEPO resin. The samples were cured in an oven at 25 ºC for 3 h and post cured at 80 ºC for 6h. The mechanical and thermal properties, morphology as well as water absorption of epoxy, epoxy/AEPO blend and epoxy/AEPO/MMT nanocomposite were studied. The obtained results showed that incorporation of 0.5 phr of MMT nanoclay in epoxy resin increased the tensile strength and modulus as well as thermal stability of the epoxy/AEPO resin. The morphology of epoxy/AEPO/MMT nanocomposite confirmed the intercalated structure of MMT nanoclay in the epoxy resin matrix. The finding proved that 0.5 phr MMT loading was sufficient to improve the mechanical and thermal properties of epoxy/AEPO resin.